Know and use your personal strengths! A Spanish validation of the strengths knowledge and use scales and their relationship with meaningful work and work-related well-being - Peláez Zuberbühler, Josefina; Coo Calcagni, Cristián; Salanova, Marisa (Frontiers in Psychology, 2023)
Research in the field of work and organizational psychology increasingly highlights the role of meaningful work as a protector of well-being at work. This study tests the role of strengths knowledge and use as new pathways through which meaningful work may have a positive effect on work engagement and mental health. Study 1 and Study 2 report the validation of the Spanish Strengths Use and Knowledge Scales respectively, with samples of N = 617 (Study 1) and N = 365 (Study 2) employees. Study 3 tests the mediating effects of strengths use and knowledge in a model with different work-related constructs in another sample of N = 798 employees. Findings from Studies 1 and 2 indicate that the instruments offer adequate evidence of reliability and validity. Results from Study 3 revealed that strengths knowledge is a mediator in the relationship between meaningful work and strengths. Findings also confirmed the mediating roles of strengths use in the relationship between meaningful work and work engagement, and between meaningful work and mental health. Conclusions: This study highlights the ability to be aware of and apply signature strengths as effective and novel pathways to foster well-being at work through the cultivation of meaningful work.